Agriculture Public Spending and Growth : The Example of Indonesia - Armas, Enrique Blanco; Osorio, Camilo Gomez; Moreno-Dodson, Blanca (World Bank, Washington, DC, 2012)
This note analyzes the trends and evolution of public spending in the agriculture sector in Indonesia, as well as its impact on the growth of agriculture during the period 1976-2006. Public spending on agriculture and irrigation had a positive impact on agriculture growth during that period, whereas public spending on fertilizer subsidies had the opposite effect. As Indonesia continues its efforts to revitalize the agriculture sector, public spending should be directed at improving the provision of public services rather than at subsidizing private inputs.